Examining Treatment Outcomes: Differences Between Primary and Non-Primary Marijuana-Using Youths Transitioning Into Recovery. Issue 4 (4th July 2017) - Gonzales, Rachel; Steinberg, Jane; Winters, Ken C.; Murphy, Debra A.; Ang, Alfonso; Hernandez, Mayra; Mugahwi, Mohammed
ABSTRACT: To date, little is known about psychosocial and behavioral effects of marijuana (MJ) use among youths in substance abuse disorder (SUD) treatment. We recruited 80 youths ( Mage = 20.4 ± 3.5 years old) to participate in an aftercare pilot program from SUD treatment programs in Southern California. This article explores differences in psychosocial and behavioral treatment outcomes between youths in SUD treatment for MJ compared to youths in treatment for another primary substance other than MJ (i.e., stimulants, opioids, alcohol). Youths in SUD treatment for MJ reported being less likely to quit, continued MJ use at treatment completion, less substance use severity, less psychosocial distress, and fewer criminal behaviors compared to youths who received treatment for substances other than MJ. There were differences in HIV-risk outcomes in the past year; however, both groups reported risky sexual behavior in the past month at treatment discharge.